Engineering the metabolic pathways of lipid biosynthesis to develop robust microalgal strains for biodiesel production. (30th September 2019) - Shahid, Ayesha; Rehman, Abd ur; Usman, Muhammad; Ashraf, Muhammad Umer Farooq; Javed, Muhammad Rizwan; Khan, Aqib Zafar; Gill, Saba Shahid; Mehmood, Muhammad Aamer
Abstract: Algal lipids have shown promising feedstock to produce biodiesel due to higher energy content, higher cetane number, and renewable nature. However, at present, the lipid productivity is too low to meet the commercial needs. Various approaches can be employed to enhance the lipid content and lipid productivity in microalgae. Stress manipulation is an attractive option to modify the algal lipid content, but it faces the drawback of time‐consuming production processing and lack of information about molecular mechanisms related to triacylglycerides production in response to stress. Developing the robust hyper lipid accumulating algal strains has gained momentum due to advances in metabolic engineering and synthetic biology tools. Understanding the molecular basis of lipid biosynthesis followed by reorienting the related pathways through genomic modification is an alluring strategy that is believed to achieve the industrial and economic robustness. This review portrays the use of integrated OMIC approaches to elucidate the molecular mechanisms of strain adaptability in response to stress conditions, and identification of molecular pathways that should become novel targets to develop novel algal strains. Moreover, an update on the metabolic engineering approaches to improve the lipid production in microalgae is also provided.